2020
DOI: 10.1128/msphere.00258-20
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for Perivascular Cells in Amplifying Vascular Leakage Induced by Dengue Virus Nonstructural Protein 1

Abstract: Dengue is the most prevalent arthropod-borne viral disease affecting humans, with severe dengue typified by potentially fatal microvascular leakage and hypovolemic shock. Blood vessels of the microvasculature are composed of a tubular structure of endothelial cells ensheathed by perivascular cells (pericytes). Pericytes support endothelial cell barrier formation and maintenance through paracrine and contact-mediated signaling and are critical to microvascular integrity. Pericyte dysfunction has been linked to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…NS1 is a glycoprotein secreted into the circulatory system as a hexamer and has been shown to induce permeability in primary human endothelial cell monolayers from a variety of organs in vitro by altering the endothelial glycocalyx [62, 63]. In addition, we recently demonstrated that the in vitro effects of DENV-2 NS1 on endothelial cells are more pronounced in the presence of primary human pericytes [64]. Treatment with recombinant soluble NS1 disrupted pericyte-endothelial cell interactions in 3D cocultures and increased barrier permeability, without affecting pericyte migration capacity or viability [64].…”
Section: Impact Of Secreted Viral Proteins On Pericytesmentioning
confidence: 99%
See 1 more Smart Citation
“…NS1 is a glycoprotein secreted into the circulatory system as a hexamer and has been shown to induce permeability in primary human endothelial cell monolayers from a variety of organs in vitro by altering the endothelial glycocalyx [62, 63]. In addition, we recently demonstrated that the in vitro effects of DENV-2 NS1 on endothelial cells are more pronounced in the presence of primary human pericytes [64]. Treatment with recombinant soluble NS1 disrupted pericyte-endothelial cell interactions in 3D cocultures and increased barrier permeability, without affecting pericyte migration capacity or viability [64].…”
Section: Impact Of Secreted Viral Proteins On Pericytesmentioning
confidence: 99%
“…In addition, we recently demonstrated that the in vitro effects of DENV-2 NS1 on endothelial cells are more pronounced in the presence of primary human pericytes [ 64 ]. Treatment with recombinant soluble NS1 disrupted pericyte-endothelial cell interactions in 3D cocultures and increased barrier permeability, without affecting pericyte migration capacity or viability [ 64 ]. These effects were mediated at least partially by the disruption of contact-independent paracrine signalling between pericytes and endothelial cells [ 64 ].…”
Section: Impact Of Secreted Viral Proteins On Pericytesmentioning
confidence: 99%
“…In vivo and in vitro studies have shown that NS1 alone (without the rest of the viral components) can increase endothelial barrier permeability and cause vascular leakage, which can be attenuated with an NS1 vaccine [78]. Cheung et al [79] also reported that NS1 specifically disrupts the ability of pericytes to support endothelial cell function in a three-dimensional microvascular assay, leading to endothelial hyperpermeability. In human endothelial cells, NS1 activates p38 mitogen-activated protein kinase and the inhibitor of this kinase reduces NS1-mediated endothelial permeability [80].…”
Section: Effects Of Non-respiratory Viruses On the Cardiovascular Sysmentioning
confidence: 99%
“…The studies by Beatty et al [78] used the dengue virus NS1 protein at 10 mg/kg body weight for mouse experiments to elicit endothelial permeability, while the studies by Kuba et al [34] used 1 mg/kg body weight of the SARS-CoV-1 spike protein to elicit the Ang II-dependent augmentation of lung injury. In cell culture studies, approximately 20 nM [78], 10 nM [79], and 200 nM [80] concentrations of dengue virus NS1 protein were used to elicit biological responses. Conversely, approximately 0.1 nM of the SARS-CoV-2 spike protein elicits biological responses [38].…”
Section: Effects Of Non-respiratory Viruses On the Cardiovascular Sysmentioning
confidence: 99%
“…Jannaway et al demonstrated that thrombin can cleave syndecan 3/4 ectodomain into fragments which interact with endothelial cells, causing paracellular hyperpermeability (15). Through contact independent signaling, this vascular leakage may be amplified by perivascular cells, such as in the case of Dengue viral protein NS1 (16).…”
Section: Introductionmentioning
confidence: 99%